Gender and developmental specific N-glycomes of the porcine parasite Oesophagostomum dentatum - Jiménez-Castells, Carmen (Biochim Biophys Acta, 2016)
BACKGROUND: The porcine nodule worm Oesophagostomum dentatum is a strongylid class V nematode rather closely related to the model organism Caenorhabditis elegans. However, in contrast to the non-parasitic C. elegans, the parasitic O. dentatum is an obligate sexual organism, which makes both a gender and developmental glycomic comparison possible. METHODS: Different enzymatic and chemical methods were used to release N-glycans from male and female O. dentatum as well as from L3 and L4 larvae. Glycans were analysed by MALDI-TOF MS after either 2D-HPLC (normal then reversed phase) or fused core RP-HPLC. RESULTS: Whereas the L3 N-glycome was simpler and more dominated by phosphorylcholine-modified structures, the male and female worms express a wide range of core fucosylated N-glycans with up to three fucose residues. Seemingly, simple methylated paucimannosidic structures can be considered ‘male’, while methylation of fucosylated glycans was more pronounced in females. On the other hand, while many of the fucosylated paucimannosidic glycans are identical with examples from other nematode species, but simpler than the tetrafucosylated glycans of C. elegans, there is a wide range of phosphorylcholine-modified glycans with extended HexNAc(2-4)PC(2-4) motifs not observed in our previous studies on other nematodes. CONCLUSION: The interspecies tendency of class V nematodes to share most, but not all, N-glycans applies also to O. dentatum; furthermore, we establish, for the first time in a parasitic nematode, that glycomes vary upon development and sexual differentiation. GENERAL SIGNIFICANCE: Unusual methylated, core fucosylated and phosphorylcholine-containing N-glycans vary between stages and genders in a parasitic nematode.